Risk factors for obstetric anal sphincter injury: To prolong or to vacuum?. (March 2016) - Garmi, Gali; Peretz, Hadar; Braverman, Meirav; Berkovich, Ilanit; Molnar, Robert; Salim, Raed
Abstract: Introduction: An awareness of risk factors for obstetric anal sphincter injuries (OASIS) is essential in order to reduce the occurrence of the primary event. These risk factors are demographic, obstetric and intrapartum related. We aimed to identify the risk factors for OASIS and to examine how modifiable risk factors may be used in order to reduce the incidence of OASIS. Methods: A retrospective, matched case–control study was conducted in the delivery ward of a single university teaching hospital in Israel, using data from January 2004 to July 2012. All singleton vaginal deliveries at term with OASIS were included. The controls included women matched at a ratio of 1:2 based on gestational age and deliveries that occurred immediately before and after the delivery of the women in the study group. Results: Overall, 113 OASIS were identified. Stepwise conditional logistic regression revealed that the first vaginal birth (OR = 7.6; 95% confidence interval (CI), 3.5–16.3; p < 0.001) particularly after a previous caesarean section (OR = 13.6; 95% CI, 4.7–39.3; p < 0.001) and the length of the second stage (OR 1.5; 95% CI, 1.1–2.1, p = 0.045) were the only risk factors for OASIS. Among 24 primiparous women who already had a prolonged second stage, 15 delivered by vacuum extraction and nine spontaneously; OASIS occurred in eight (53%) and three (33%) women, respectively. Multivariate analysis showed that this difference was not significant (OR = 2.3; 95% CI, 0.4–12.7; p = 0.35). Conclusions: The first vaginal birth particularly after a caesarean delivery and the length of the second stage increased the risk of OASIS. Vacuum extraction performed to shorten a prolonged second stage is not necessarily protective. Highlights: The first vaginal birth particularly after a caesarean delivery is a risk factor for sphincter injury. The length of the second stage is a risk factor for obstetric anal sphincter injury. Vacuum extraction performed to shorten a prolonged second stage is not necessarily protective.